Perceção do consumidor final de energia sobre redes inteligentes e a sua participação ativa - Luís Filipe de Oliveira Gomes (2020)
The paradigm of energy systems is changing. The appearance of smart grids will change the role of the end-user, taking an active role in smart grids. This change will have a significant impact on the end-user, affecting consumption and energy management habits. Failure to prepare the end-user for the changes that will come will have a negative impact and an increase in energy costs. Therefore, it is essential to study the perception of current energy end-users about smart grids. This thesis aims to study the perception of the end-user and to study the impact that this perception will have on the smart grid. An end-user survey will be conducted to study and assess their perception of smart grids and the active participation of the end-user in smart grids. This thesis will also develop a simulator that will allow evaluating the active participation of end-users taking into account the carried-out survey. The simulator will allow the study of several scenarios and will allow the comparison of different levels of participation. The comparison of the results of the simulations will allow the identification of which points hinder the active participation of the end-users. As a result, this thesis will develop a communication strategy with the end-user to promote and maximize their active participation in smart grids. The communication strategy will take into account the result of the survey and the results of the simulations.